Lymphoma Immunophenotype of Dogs Determined by Immunohistochemistry, Flow Cytometry, and Polymerase Chain Reaction for Antigen Receptor Rearrangements. (20th September 2013) - Thalheim, L.; Williams, L.E.; Borst, L.B.; Fogle, J.E.; Suter, S.E.
<x xml:space="preserve">Abstract</x> Background Immunohistochemistry (IHC), flow cytometry (FC), and PCR for antigen receptor rearrangements (PARR) are 3 widely utilized tests to determine immunophenotype in dogs with lymphoma (LSA). Objectives This study evaluated the ability of FC and PARR to correctly predict immunophenotype as defined by IHC and to determine the level of agreement among the 3 tests. Animals Sixty‐two dogs with lymphoma. Methods Retrospective study. Medical records were searched to identify dogs with LSA that had concurrent IHC, FC, and PARR performed. Immunophenotype results were categorized as B‐cell, T‐cell, dual immunophenotype (B‐ and T‐cell), or indeterminate. The results of FC and PARR were evaluated for correctly classifying B‐ and T‐cell LSA as compared with IHC. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were evaluated in addition to concordance between each test. Results The sensitivity of FC was significantly higher than PARR for both B‐cell (91% versus 67%; P < 0.0072) and T‐cell (100% versus 75%; P < 0.0312) LSA. The percent agreement between FC and IHC was 94%, between PARR and IHC was 69%, between FC and PARR was 63%, and among all 3 tests was 63%. Conclusions and Clinical Importance Flow cytometry is superior to PARR in correctly predicting immunophenotype when evaluating lymph nodes from dogs already diagnosed with B‐ or T‐cell LSA. If fresh samples are not available for FC, PARR is an acceptable assay for determination of immunophenotype given its high specificity.